Co‐circulation and characterization of HPAI‐H5N1 and LPAI‐H9N2 recovered from a duck farm, Yogyakarta, Indonesia. Issue 2 (16th December 2019) - Lestari,; Wibawa, Hendra; Lubis, Elly Puspasari; Dharmawan, Rama; Rahayu, Rina Astuti; Mulyawan, Herdiyanto; Charoenkul, Kamonpan; Nasamran, Chanakarn; Poermadjaja, Bagoes; Amonsin, Alongkorn
Abstract: In July 2016, an avian influenza outbreak in duck farms in Yogyakarta province was reported to Disease Investigation Center (DIC), Wates, Indonesia, with approximately 1, 000 ducks died or culled. In this study, two avian influenza (AI) virus subtypes, A/duck/Bantul/04161291‐OR/2016 (H5N1) and A/duck/Bantul/04161291‐OP/2016 (H9N2) isolated from ducks in the same farm during an AI outbreak in Bantul district, Yogyakarta province, were sequenced and characterized. Our results showed that H5N1 virus was closely related to the highly pathogenic AI (HPAI) H5N1 of clade 2.3.2.1c, while the H9N2 virus was clustered with LPAI viruses from China, Vietnam and Indonesia H9N2 (CVI lineage). Genetic analysis revealed virulence characteristics for both in avian and in mammalian species. In summary, co‐circulation of HPAI‐H5N1 of clade 2.3.2.1c and LPAI‐H9N2 was identified in a duck farm during an AI outbreak in Yogyakarta province, Indonesia. Our findings raise a concern of the potential risk of the viruses, which could increase viral transmission and/or threat to human health. Routine surveillance of avian influenza viruses should be continuously conducted to understand the dynamic and diversity of the viruses for influenza prevention and control in Indonesia and SEA region.